Pterygium excision with conjunctival autografting: an effective and safe technique. Issue 11 (November 1993) - Allan, B D; Short, P; Crawford, G J; Barrett, G D; Constable, I J
Abstract : The optimum mode of treatment for symptomatic pterygia would combine efficacy (a low recurrence rate) with safety (freedom from sight threatening complications), and would not affect visual acuity adversely. The efficacy of pterygium excision with conjunctival autografting in a sun exposed population in which pterygia are prevalent has previously been questioned. A cross sectional review of 93 eyes of 85 patients was carried out by slit-lamp examination a minimum of 6 months (range 6-76 months) after pterygium excision and free conjunctival autografting. Case notes were reviewed to obtain details of complications and visual acuity changes related to surgery. Of six recurrences (6.5%) four of these were asymptomatic with minor recurrences. Two patterns of recurrence were identified: cross graft recurrence (three cases) and outflanking (three cases). Complications (wound dehiscence, three cases; Tenon's granuloma one case; conjunctival cyst, one case) were all corrected by minor surgical revision without sequelae. Unaided acuities were unchanged or improved 3 months after surgery in 86 cases, with a minor diminution (1 Snellen line) in seven cases. This study demonstrates a low recurrence rate for a safe technique in an area in which ongoing ultraviolet light exposure levels are high and pterygia are prevalent.